Perkembangan Kognitif: Meningkatkan Keterampilan Klasifikasi pada Anak Usia 5-6 Tahun Melalui Pembelajaran Manipulatif Terstruktur.pdf - Muqimah Surganingsih; Azizah Amal; Nurul Indah Ramadani; Fadhilah Afifah; Febriana Ekananda Suras (Ihya Ulum: Early Childhood Education Journal, 2026)
Classification is a foundational cognitive skill required for early mathematics, yet children aged 5–6 years often struggle to transition from single-criterion to dual-criterion sorting due to cognitive centration. This study evaluates the effectiveness of a structured manipulative intervention, specifically the Shape and Color Sorting activity, in enhancing these skills. A quantitative approach with a pre-experimental, one-group pretest-posttest design was employed. Through total sampling, 20 children from Group B in Raudhatul Jannah Katangka Kindergarten were selected. Data gathered via structured pretest and posttest rubrics were analyzed using descriptive statistics, parametric assumption tests (normality and homogeneity), a paired samples t-test, and a simple linear regression analysis. Descriptive findings indicated substantial improvement in classification performance, shown by an increase in the mean conceptual score from 54.30 (±8.14) in the pretest to 66.95 (±7.63) in the posttest. The inferential analysis via a paired samples t-test confirmed this improvement was highly significant (t=3.632; df=19; p=0.001), proving that structured manipulative activities systematically reduced the children's cognitive centration. Furthermore, regression analysis demonstrated that initial baseline skills contributed 26.8% to the variance of posttest outcomes (R2=0.268; p=0.019). These findings conclude that structured manipulative activities are effective in expanding early childhood classification capacities. This study provides practical implications for early childhood educators to integrate multi-criteria manipulative sorting games within the curriculum to systematically support abstract logical reasoning and cognitive readiness.